Life cycle assessment of an ecological living module equipped with conventional rooftop or integrated concentrating photovoltaics. (31st March 2021) - Raugei, Marco; Keena, Naomi; Novelli, Nick; Aly Etman, Mohamed; Dyson, Anna
Abstract: Climate change is disrupting our environment and business‐as‐usual practices will fail to reverse its impact. This paper focuses on the impact of the building sector and, in particular, it questions the energy and environmental benefits of advanced integrated and more conventional building‐applied photovoltaic (PV) systems, compared to a traditional municipality utility supply. A demonstration project named the ecological living module (ELM) is used to create a comparative life cycle assessment (LCA) of the adoption of these PV systems across three different climatic locations, namely New York City, London, and Nairobi. Findings show that, over the entire life cycle, the solar systems do better than the grid mix in reducing the building's dependence on nonrenewable resources. Unsurprisingly, in comparative terms, these systems do substantially better if the local grid mix is characterized by a predominantly nonrenewable energy profile. When comparing the two solar systems, the environmental impacts of the solar cells are negligible in the advanced system, whereas its structural components result in it being less environmentally friendly than the conventional solar PV. This highlights the possibility of future design iterations of these components to rethink their material ecology in terms of their life cycle—materiality, sourcing, and manufacturing, and so forth. The implications of this work suggest questioning, on a case‐by‐case basis, when and in what contexts integrated solar energy building systems are most plausible. This work also questions the scale at which grid scale distribution should occur.